2019
DOI: 10.1103/physrevmaterials.3.125601
|View full text |Cite
|
Sign up to set email alerts
|

Lattice vibrations ofγ- andβ-coronene from Raman microscopy and theory

Abstract: We combine polarization-resolved low frequency Raman microscopy and dispersion-corrected density-functional calculations (DFT-D3) to study polymorph-dependent lattice vibrations in coronene, a model molecular system for nanographenes and disc-like organic semiconductors that exhibits two crystalline structures with distinct electronic and optical properties. Changes in low energy Raman-active lattice phonons are followed across the γ-to β-phase transition at 150 K. Raman frequencies calculated using DFT-D3 agr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Moreover, ab initio modeling techniques have recently been employed in predicting phonon-related spectra, including Raman, and infrared, facilitating the usage of theory to interpret experiments. A large and growing body of the literature covers the prediction of vibrational modes and Raman spectra from first-principle techniques, , providing a valuable aid to experimental characterization. For example, a recent theoretical work reported Raman spectra of six Bi-O-X materials with similar layer crystal structures: Bi 2 O 2 X and Bi 2 OX 2 (X = S, Se, and Te), which could help to identify the crystal structures experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ab initio modeling techniques have recently been employed in predicting phonon-related spectra, including Raman, and infrared, facilitating the usage of theory to interpret experiments. A large and growing body of the literature covers the prediction of vibrational modes and Raman spectra from first-principle techniques, , providing a valuable aid to experimental characterization. For example, a recent theoretical work reported Raman spectra of six Bi-O-X materials with similar layer crystal structures: Bi 2 O 2 X and Bi 2 OX 2 (X = S, Se, and Te), which could help to identify the crystal structures experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…At 0.2 GPa, two lattice modes (L 1 and L 2 ), which were particularly sensitive to phase transitions, split into doublets producing a spectrum that was a fingerprint of the β ‐polymorph. [ 19,27 ] The polymorph change at 0.2 GPa, coincided with a sharp increase in the PL intensity observed at the same pressure. At 0.8 GPa, the L 2a peak split and formed another doublet, indicating a structural change.…”
Section: Resultsmentioning
confidence: 55%
“…The properties are calculated with the PBE functional, with relative lattice energies including the three specified dispersion corrections. The experimental temperature range of stability is from ref .…”
Section: Resultsmentioning
confidence: 99%
“…The size of a β coronene a crystal grown under a magnetic field 35 was sufficient to establish its structure by single-crystal X-ray diffraction. Calculation of the Raman spectra of the two forms has shown that the β form is the more stable phase of coronene at low temperatures, 37,38 which had not previously been characterized because the γ crystals shatter on cooling. Examination of the phase transition in different samples (SI, Section I.D) shows that the polymorphic transformation is dependent on crystal size.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
See 1 more Smart Citation